ANALISIS DAMPAK SUBSIDI HARGA PUPUK TERHADAP OUTPUT SEKTOR PRODUKSI DAN TINGKAT PENDAPATAN RUMAH TANGGA DI JAWA TENGAH (Pendekatan Analisis I-O dan SNSE Jawa Tengah Tahun 2004) - Kasiyati, Sri; Santosa, Purbayu Budi (Jurnal Organisasi dan Manajemen, 2010)
This research aims to know the impact of price subsidy on change in output of product sector as well as the influence of the subsidy on the level of household income in Central Java. This research used input-output and SAM (Social Accounting Matrix) analysis. To analyze the impact of fertilizer price subsidy on the changes in output, this research used supply side aproach with matrix output inverse. While to know fertilizer price subsidy on household income, this research used SAM analysis analysis that stimulated the impact of fertilize price by income distribution patern analysis by using Matrix Decomposition Analysis. The research to referred SNSE Central Java 2004. The findings showed that fertilizer price subsidy in Central Java 2008 affected changes in output. The sector that showed highest changes was chemistry industrial and fertilizer sector (Rp 2.122.497 million), followed by mining sector ( Rp 1.274.906 million). Subsidy of fertilizer price in Central Java also affected the total increase in household income in Central Java (0,6435 percents). The household that showed income increases was simulation analysis was farmer entrepreneur household that showed income increase Rp 257.288,92 million or rise as high as 0,6024 percents. The second highest increase was urban affairs upper crust household with value of Rp 257.046,84 million.